Alternative Augmentative Communication "Wofal" for Children with Down Syndrome - Yuli Afmi Ropita Sari; Rini Lestari; Neneng Maya Komalasari (Indonesian Journal of Disability Studies, 2021)
This research is motivated by the existence of communication problems in children with Down syndrome. Communication problems on the subject are related to the use of language in their environment. The data obtained from the subject's parents, teachers and tutors experienced problems in expressing their own desires. The purpose of this study is to help subjects communicate with their environment. Communication uses tools that are made based on the needs and abilities of the current subject. The tool created is called "Wofal". This tool is in the form of modified images with an attractive shape and easy to use subjects. The first stage of using the tool introduces the images that the subject will use in communicating. Second, the subject was asked to stick to his wishes and choose an image. The picture consists of the subjects' daily activities at home and at school. After intervention to the subject, the results were obtained. According to teachers, parents and tutors, this tool makes it easier for subjects to communicate. Usually teachers, tutors and parents do not understand what the subject wants. After this tool the crying behavior of the subject became less. So, this tool makes it easier for subjects to communicate in their environment.